Vom Prompt zur Praxis – Kooperatives Seminarkonzept zur KI-gestützten Unterrichtsentwicklung in der gewerblich-technischen Lehramtsausbildung - Schäfers, Johannes; Vernholz, Mats; Jonas-Ahrend, Gabriela; Temmen, Katrin

Guidance on Dataspaces: Development of a Learning Environment for Industrial SMEs - Lick, Jonas; Lamarz, Jessica; Dohmann, Friederike; Kulkarni, Pranav Jayant; Zerbin, Julian; Koldewey, Christian (2024 6th International Conference on Control and Robotics (ICCR))
The rapid advancements in digital transformation have led to the emergence of dataspaces as a pivotal element for industry-wide and cross-industry data integration and interoperability across various businesses. Despite their potential, the adoption and effective utilization of dataspaces by business stakeholders remain challenging. This paper aims to address this gap by developing a comprehensive learning environment tailored for business stakeholders. Through an interview study and an analysis of the current state of research, we identify problem fields and derive key requirements for the development of the learning environment. The proposed environment includes a demonstrator and a training concept designed to enhance stakeholders' understanding and capabilities in managing and leveraging dataspaces. Our findings contribute to the body of knowledge by providing practical guidance through learning environments for the deployment of dataspaces in business contexts and highlighting areas for future research.

Untersuchung von Kombinationen aus Duroplasten und Elastomeren für den einstufigen 2K-Spritzgießprozess - Löhr, Florian; Moritzer, Elmar; Klie, Benjamin; Giese, Ulrich (Technomer 2025 - 29. Fachtagung über Verarbeitung und Anwendung von Polymeren)
Keywords: BMC; Duroplast; Kautschuk; Mehrkomponenten; Spritzgießen

Direkthaftung statt Klebstoff –Verbund von Duroplasten und Kautschuk im 2K-Spritzgießprozess - Löhr, Florian (AZuR-Kolloquium 2025)

Thermoset–Rubber 2K Composite Systems: Material Combinations and Interfacial Reactions in a One-Step Injection Molding Process - Löhr, Florian; Moritzer, Elmar; Klie, Benjamin; Giese, Ulrich (International Rubber Conference (IRC) 2025, Bangkok, BITEC; e-abstract book)
Keywords: BMC; Duroplast; Kautschuk; Mehrkomponenten; Spritzgießen

Improvement of a numerical two-phase simulation model for single-screw plasticizing extruders based on experimental investigations - Knaup, Felix; Schöppner, Volker (International Polymer Processing)
Keywords: CFD simulation; melting modeling; melting process; polymer extrusion; single-screw extruder

Improving an Analytical Model of Melting in Single Screw Extruders considering the Delay Zone Length - Knaup, Felix; Brüning, Florian; Schöppner, Volker (Annual Technical Conference of the Society of Plastics Engineers (ANTEC 2025))
Keywords: Aufschmelzen; Aufschmelzmodellierung; delay zone; extrusion; melting modeling

Bestimmung der Feststoffbettfestigkeit zur Vorhersage von Feststoffbettbrüchen im Einschneckenextruder - Knaup, Felix; Brüning, Florian; Schöppner, Volker (Technomer 2025 29. Fachtagung)
Keywords: Aufschmelzen; Aufschmelzmodellierung; Feststoffbett; melting modeling

Characterization of the wall slip behavior of filled rubber compounds considering the critical wall shear stress - Kleinschmidt, Dennis; Schöppner, Volker (RubberCon 2025)
Keywords: Kautschuk; Rheologie; Wandgleiten

Findings on pinless screw design for rubber extrusion - Schmidt, Leon; Schöppner, Volker; Brüning, Florian (RubberCon 2025)
Keywords: extrusion; Kautschuk; Simulation

Investigation of alternative pinless screw concepts for rubber extrusion - Schmidt, Leon; Brüning, Florian (KGK - Kautschuk Gummi Kunststoffe)
Keywords: extrusion; Kautschuk

Consideration of modeled pressure dependent viscosity data in injection molding simulation - Hanselle, Felix Paul; Schöppner, Volker; Brüning, Florian (International Polymer Processing)
Keywords: Druckabhängigkeit; Rheologie; Simulation; Spritzgießen; Viskosität

Influence of pre-shearing on the rheological properties of filled rubber compounds - Kleinschmidt, Dennis; Brüning, Florian (KGK Kautschuk Gummi Kunststoffe)
Keywords: Rheologie; Viskosität; Wandgleiten

Beschreibung des Mischverhaltens von Kautschukstiftextrudern mittels simulativer und experimenteller Methoden - Kleinschmidt, Dennis (Extrusion - Grundlagen und Praxis)

Analyse des thermo-chemischen Devulkanisationsverhaltens von SBR-basierten GTR-Mischungen - Petzke, Jonas Dirk Rudolf Helmut (AZuR-Kolloquium 2025)

Improvement of injection molding simulations by application of modeled pressure dependent viscosity data - Hanselle, Felix Paul

Degradation of Polypropylene and Polypropylene Compounds on Co-Rotating Twin-Screw Extruders - Albrecht, Paul; Altepeter, Matthias; Brüning, Florian (Polymers)
The degradation of polypropylene (PP) through thermal and mechanical stress, as well as the influence of oxygen, are unavoidable when processing on a co-rotating twin-screw extruder. In previous studies, a mathematical model was developed to predict the degradation while compounding on different twin-screw extruder sizes. Additionally, the examination of filled PPs was conducted. To this end, a range of operating parameters and extruder sizes were used to process PP, and the molar mass was then determined by melt flow rate (MFR) and gel permeation chromatography (GPC) measurements to derive the degree of degradation. The model was then modified by adjusting the sensitivity parameters to allow the degradation behavior of the PPs to be described independently of extruder size. Consistent with prior research, comprehensive measurements of a PP/titanium dioxide (TiO2) compound revealed that, with a few exceptions, increasing temperatures and screw speeds and decreasing throughputs generally resulted in higher degradation. However, the application of the model to the compounds did not achieve good agreement with the measured degradation, indicating different degradation conditions due to the different thermodynamic and rheological properties of the compounds.

NUMERICAL AND EXPERIMENTAL CONSIDERATIONS OF THE CREEP OF THERMOPLASTIC FLANGE SYSTEMS FOR THE DEVELOPMENT OF AN ANALYTICAL CALCULATION METHOD - Moritzer, Elmar; Bartmann, Finn; Riedl, Alexander (Proceedings of the ASME 2025 Pressure Vessels & Piping Conference PVP2025)

Einfluss von FFF-Prozessparametern auf die elektrische Leitfähigkeit von leitfähigen TPE-Komposite - Salm, Maximilian Karl Franz; Moritzer, Elmar (Technomer 2025 29. Fachtagung)
Keywords: Additive Fertigung; Elektrische Leitfähigkeit; Compounds; TPE; Fused Filament Fabrication

Einfluss der Schichtstruktur auf die Druckfestigkeit von FDM-Bauteilen – Ein konzeptioneller Ansatz - Beutelspacher, Jonas; Scharwald, David; Moritzer, Elmar (Technomer 2025 29. Fachtagung)